Robust sensor fault estimation for descriptor-LPV systems with unmeasurable gain scheduling functions: Application to an anaerobic bioreactor - López-Estrada, Francisco-Ronay; Ponsart, Jean-Christophe; Theilliol, Didier; Astorga-Zaragoza, Carlos-Manuel; Camas-Anzueto, Jorge-Luis (Zielona Góra: Uniwersytet Zielonogórski)
This paper addresses the design of a state estimation and sensor fault detection, isolation and fault estimation observer for descriptor-linear parameter varying (D-LPV) systems. In contrast to where the scheduling functions depend on some measurable time varying state, the proposed method considers the scheduling function depending on an unmeasurable state vector. In order to isolate, detect and estimate sensor faults, an augmented system is constructed by considering faults to be auxiliary state vectors.
Keywords: fault diagnosis; fault estimation; LPV systems; observer design; descriptor systems